A 3-level integrated lot sizing and cutting stock problem applied to a truck suspension factory - Andrade, Pedro Rochavetz de Lara [UNESP]; De Araujo, Silvio Alexandre [UNESP]; Cherri, Adriana Cristina [UNESP]; Lemos, Felipe Kesrouani [UNESP] (Springer Nature, 2025)
This paper studies the process of cutting steel bars in a truck suspension factory with the objective of reducing its inventory costs and material losses. A mathematical model is presented that focuses on decisions for a medium-term horizon (4 periods of 2 months). This approach addresses the one-dimensional 3-level integrated lot sizing and cutting stock problem, considering demand, inventory costs and stock level limits for bars (objects-level 1), springs (items-level 2) and spring bundles (final products-level 3), as well as the acquisition of bars as a decision variable. The solution to the proposed mathematical model is reached through an optimization package, using column generation along with a method for achieving integer solutions. The results obtained with real data demonstrate that the method provides significantly better solutions than those carried out at the company, whilst using reduced computational time. Additionally, the application of tests with random data enabled the analysis of both the effect of varying parameters in the solution, which provides managerial insights, and the overall performance of the method.
Keywords: 3-Level integrated problem; Column generation; Lot sizing problem; Mathematical modeling; One-dimensional cutting stock problem; Truck suspension factory